Global, regional, and national consumption of controlled opioids: a cross-sectional study of 214 countries and non-metropolitan territories - Richards, GC; Aronson, JK; Mahtani, KR; Heneghan, C (SAGE Publications, 2021)
Introduction: The consumption of opioids has increased globally since the 1990s. Previous studies of global opioid consumption have concentrated on morphine alone or a subset of opioids, with a focus on cancer pain and palliative care. In this study, we have determined the global, regional, and national consumption of all controlled opioids, including anaesthetics, analgesics, antidiarrheals, opioid substitution therapies, and cough suppressants.